Cone Beam Computed Tomography based evaluation of position of mental foramen and its relation to apices of mandibular posterior teeth in a sample of Pakistani population - Momina Anis Motiwala; Faizan Javed; Robia Ghafoor (Journal of the Pakistan Medical Association, 2022)
Objective: To radiographically determine the mental foramen position, its distance to the nearest apex and the prevalence of anterior loop of mandibular nerve using cone-beam computed tomography scans. Method: The cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, from January to June 2020, and comprised cone-beam computed tomography scans of males or females of Pakistani origin aged 15-65 years with intact mandibular dentition and fully formed roots with matured apex. The scans were analysed to determine the horizontal position of mental foramen and to classify it according to the Tebo and Telford classification. The vertical distance from mental foramen to the nearest tooth apex was measured and the mandibular nerve configuration was determined. Data was analysed using SPSS 23. Results: Among the 96 scans, the most frequent location of mental foramen MF was along the long axis of 2nd premolars for both right 50(52.1%) and left 49(51%) sides, followed by between 1st and 2nd premolars for both right 28(29.2%) and left 38(39.6%) sides. The mean minimum distance from mental foramen to the nearest root apex was 3.75±2.59mm and 3.99±2.26mm on right and left sides, respectively. There was bilateral symmetry on both sides. The most frequent mandibular nerve configuration on the right 69(72.6%) and left 75(78.1%) sides, with anterior loop being the least common; right side 3(3.2%) and 5(5.2%) left side. Conclusion: The most common position of mental foramen was along the long axis of 2nd premolars while the anterior loop was the least common. Key Words: CBCT, Mental foramen, Mandibular teeth, Pakistani population, Tebo and Telford classification, Mandibular nerve.